2012
DOI: 10.1088/0953-8984/24/43/435803
|View full text |Cite
|
Sign up to set email alerts
|

Plasma frequency and dielectric function dependence on doping and temperature for p-type indium phosphide epitaxial films

Abstract: The optical properties of p-type InP epitaxial films with different doping concentrations are investigated by infrared absorption measurements accompanied by reflection and transmission spectra taken from 25 to 300 K. A complete dielectric function (DF) model, including intervalence band (IVB) transitions, free-carrier and lattice absorption, is used to determine the optical constants with improved accuracy in the spectral range from 2 to 35 μm. The IVB transitions by free holes among the split-off, light-hole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…The carrier concentration can be further estimated from experimental data by applying the Drude–Lorentz model or the Pisarenko relationship . Properties of degenerate semiconductors such as In 2 O 3 :Sn (ITO) and InP have been successfully modeled using the Drude–Lorentz model, while the Pisarenko relationship has been used for thermoelectric materials such as PbTe and Cu 2 GeS 4 . The Drude–Lorentz model is specified as ωnormalp=Enormalph=Nqnormal2ϵ0ϵmnormal*where ω p is the plasma angular frequency, E p is the plasma energy centered at 0.8 eV in the absorbance plot shown in Figure b, h is Planck's constant, N is the carrier concentration, q is the elementary charge, ϵ 0 is the dielectric constant of free space, ϵ ∞ is the high frequency relative dielectric constant equal to 8.1 for Cu 12 Sb 4 S 13 , and m* is the hole effective mass estimated from band structure assessment as 1.3 m e .…”
Section: Resultsmentioning
confidence: 99%
“…The carrier concentration can be further estimated from experimental data by applying the Drude–Lorentz model or the Pisarenko relationship . Properties of degenerate semiconductors such as In 2 O 3 :Sn (ITO) and InP have been successfully modeled using the Drude–Lorentz model, while the Pisarenko relationship has been used for thermoelectric materials such as PbTe and Cu 2 GeS 4 . The Drude–Lorentz model is specified as ωnormalp=Enormalph=Nqnormal2ϵ0ϵmnormal*where ω p is the plasma angular frequency, E p is the plasma energy centered at 0.8 eV in the absorbance plot shown in Figure b, h is Planck's constant, N is the carrier concentration, q is the elementary charge, ϵ 0 is the dielectric constant of free space, ϵ ∞ is the high frequency relative dielectric constant equal to 8.1 for Cu 12 Sb 4 S 13 , and m* is the hole effective mass estimated from band structure assessment as 1.3 m e .…”
Section: Resultsmentioning
confidence: 99%
“…The temperature dependence of ½ p , ¸, and ¾ ¨for Ag and Au have been studied from room temperature to 650 K. Free-carrier intra-band absorption is an indirect process and is mediated by phonons providing the additional momentum required for the energy and momentum conservation and are responsible for the temperature dependence of optical properties of the material. 22) It is found that the experimental temperature-dependent ½ p , ¸, and ¾ ¨are fitted using the following empirical functions: 23)…”
Section: Temperature Dependent Propertiesmentioning
confidence: 99%
“…However, higher electron concentrations result in higher plasma frequencies, 36 limiting the optical transparency of incident light in the MWIR range. The dependency of plasma frequency on carrier concentration is provided by the following equation: 45 where n e is the carrier concentration, e is the charge of the carriers, m * is the effective mass of the carriers, and ε 0 is the permittivity of free space.…”
Section: Resultsmentioning
confidence: 99%